Educação ambiental voltada à conservação das tartarugas marinhas no município de Maxaranguape, RN no contexto do ensino de biologia - Câmara, Rodrigo Cássio Rosendo da (2024)
Sea turtles are on the list of endangered animals, they are vertebrate animals belonging to the oldest lineage of living reptiles, which contribute to the balance of the marine ecosystem, the health and maintenance of coral reefs, estuaries and sandy beaches. Pollution of the seas, the slaughter of females and collection of eggs, capture through fishing gear, vehicle traffic in spawning areas are examples of threats to these reptiles. In Rio Grande do Norte (RN), the municipality of Maxaranguape has beaches with occurrences of laying and nesting of sea turtles of the species hawksbill turtle (Eretmochelys imbricata), green turtle (Chelonia mydas) and olive turtle (Lepidochelys olivácea), with records of conservation actions carried out by local entities. This research aimed to develop, based on biology teaching, Environmental Education activities aimed at the conservation of sea turtles in the municipality of Maxaranguape, RN. The study, characterized as qualitative and quantitative, was carried out with high school students in a public basic education school. The methodological strategy was participant research, and data were obtained from participant observation, application of questionnaires and conversation circles. The activities took place during classes in the academic year in 2023, in which studies on the conservation of sea turtles were organized in a Didactic Sequence, under the approach of teaching through investigation, with active methodologies, with the following pedagogical strategies: dialogued exhibition, classroom of flipped classes, field studies and seminars. The students actively participated, taking a leading role in carrying out studies and research, building arguments and deepening their concepts about environmental conservation aimed at preserving sea turtles. Contents such as: turtle life cycle, main threats to their conservation, and conservation actions were worked on from a scientific research perspective contextualized to the students' reality. The research path was systematized in a pedagogical product entitled “Educational Guide for the Conservation of Sea Turtles in Maxaranguape, RN”, guiding studies and actions that encourage environmental awareness in relation to the conservation of turtles in the municipality, generating knowledge about their ecology, biology and importance socio-environmental for biodiversity, local culture and the marine environment. It is also the purpose of the study to make this guide available to basic education teachers, presenting suggestions for a pedagogical path in approaching the conservation of sea turtles in high school biology classes.